Exploring Chinese EFL teachers' knowledge and beliefs relating to the teaching of English reading in public primary schools in China. (15th August 2019) - Luo, Meina; Main, Susan; Lock, Graeme; Joshi, R. Malatesha; Zhong, Chenyin
Abstract : The present study explored knowledge and beliefs about reading instruction of Chinese teachers teaching English as a foreign language (EFL). Theoretical Orientation to Reading Profile and the Survey of Basic Language Constructs Related to Literacy Acquisition were administered to 262 EFL teachers in the south‐eastern part of China. Additionally, three teachers were interviewed, and their instructional practices were observed. The results showed that there was no correlation between teachers' self‐efficacy beliefs and the performance on the knowledge of basic language construct survey. However, it was found that teachers' knowledge, beliefs, and instructional practices were mediated by the Chinese EFL contextual factors. Educational and practical implications are discussed.